Restructuring of the Electricity Industry and Environmental Issues: A California Research Program - Edward L. Vine (The Scientific World Journal)
As part of the restructuring of the electricity industry in many states, public benefits funding has emerged as a primary mechanism for supporting social benefits such as energy efficiency and research and development (R&D). In California, a Public Interest Energy Research (PIER) Program was established to conduct public interest energy research that seeks to improve the quality of life for Californias citizens by providing environmentally sound, safe, reliable, and affordable energy services and products. PIER includes the full range of research, development, and demonstration activities that will advance science or technology not adequately provided by competitive and regulated markets. The PIER Program is comprised of six PIER Program funding areas, including the Energy-Related Environmental Research. The overall mission of the Energy-Related Environmental Research is to Develop cost-effective approaches to evaluating and resolving environmental effects of energy production, delivery, and use in California, and explore how new energy applications and products can solve environmental problems. This paper describes the process used in developing these approaches and identifies a set of environmental issues that the State plans to evaluate.